Multiphase and multicomponent flows simulation using mesoscale method - Gong, Wei (2019)
The main work in this thesis is to use lattice Boltzmann (LB) method to solve multiphase and multi-component problems in mesoscale. The practical problems include water droplet wetting states transitions, oil droplets motions in water under electric field, and three stages of boiling. Besides, a multi-bubble/droplet coexistence problem for single component multiphase (SCMP) LB model has also been investigated. In the wetting transition work, the free energy curves based on the transition processes are presented and discussed in detail. The existence of energy barriers with or without consideration of the gravity effect, and the irreversibility of wetting transition are discussed based on the presented energy curves. The energy curves show that different routes of the Cassie-to-Wenzel transition and the reverse transition are the main reason for the irreversibility. Numerical simulations are implemented via a phase field LB method of large density ratio, and the simulation results show good consistency with the theoretical analysis. Through the numerical analysis, the proposed energy curves can be verified to a great degree, and it verifies that the Wenzel-to-Cassie transition can happen spontaneously without any external forces if the intrinsic Young’s angle is large enough. Besides, the critical state energy in the energy curves can be increased by modifying the micro posts to achieve a much better super-hydrophobicity. In the oil-in-water work, a multi-component multiphase (MCMP) LB model is proposed by coupling the LB scheme electrostatic field equation to simulate oil droplets motions in water under electrostatic field. Single water droplet deformation and double water droplets attracting each other in oil under strong electric field are accomplished using this model. The numerical simulation results are compared with previous experiment results and it shows a good agreement between them, which means the proposed model is eligible to be used to study the dielectrophoresis force effect on oil/water separation. The dielectrophoresis force effect on oil droplets in water is studied. The result shows that dielectrophoresis force has effect on oil droplets in water under weak electric field and it can promote the oil droplets coalescence, which can be helpful for down-hole oil water separation (DOWS) in a hydrocyclone. Experiment study has also been carried out, however, the dielectrophoresis force effect is not observed due to devices constraints and the quite weak dielectrophoresis force. Nevertheless, the electroosmosis phenomenon is observed in the experiment and it drives the oil droplets moving in an ordered way. In the boiling work, a modified improved SCMP LB model for phase change heat transfer is proposed. The boiling phenomenon in three stages: nucleate boiling, transition boiling and film boiling are accomplished using LB model. The numerical model is validated with liquid-vapour coexistent densities, D2 law for droplets evaporation as well as the three boiling stages. Compared with the original pseudopotential phase change model, the modified model has a better accuracy and can be used to study phase change physics problems including evaporation and boiling heat transfer. In the multi-bubble/droplet coexistence problem work, the thermal immiscible multiphase flow simulation using pseudopotential LB method is studied. The results show that it is difficult to achieve multi-bubble/droplet coexistence due to a mass transfer phenomenon of “the big eat the small” – the small bubbles/droplets disappear and the big ones getting bigger before a physical coalescence when using an internal energy-based temperature equation for single component multiphase (SCMP) pseudopotential models. In the present study, the mass transfer phenomenon between vapour phase and liquid phase is investigated, and the possible reason is explored. It is found that there is a spurious flow field formed between two bubbles or droplets with different shapes, and such flow field is exactly the transfer of high-density mass. In addition, it is found that the curvatures of the interfaces determine the direction of the spurious flow field, and for the definition of “the big eat the small”, “the big” refers to the interfaces that have larger radii of curvature while “the small” represents the interfaces with smaller radii of curvature. MCMP LBM is also tested in this work and it is found to be free of the unphysical mass transfer. In addition, this unphysical effect can be effectively impeded by coupling an entropy-based temperature field, and the influence on density fields with different energy equations are discussed. This work gives a significant inspiration for solving the mass transfer problem between two phases, which determines whether the SCMP LB model can be used for multibubble/droplet systems.